Pengaturan Tentang Visa Kunjungan dan Dampaknya Bagi Pekerja Yang Unprosedural - Soumena, Firma Riza Aksamilani; Anwar, Arman; Rehatta, Veriena Josepha Batseba (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: A visit visa is a visa granted to a foreigner who will travel to a part of the country for a visit for the purpose of government duties, education,socio-culture, tourism, pre-investment, business, family, journalism, or to stop for a moment to continue traveling to another country. However, the fact is that visiting visas are often misused by people in other countries, one of  which is unprosedural workers. Purposes of the Research:  To find out the arrangements regarding visit visas in immigration law and to find out the use of a visit visa and its impact on unprocedural workers.Methods of the Research: This study uses a normative juridical research method with legal materials used, namely primary legal materials and tertiary legal materials. The collection technique was carried out through a literature study and then analyzed using qualitative methods.Results of the Research: The results of the study show that a visit visa as a condition for traveling to a country cannot be used for other purposes. With the existence of immigration law actions both in administrative and criminal forms issued by each country, it is an appropriate legal action in giving sanctions to perpetrators of abuse of visit visas, especially for unprocedural workers.